Horse - Walker, Elaine, 1960- (Animal (Reaktion Books), 2008)
"From Pegasus to Black Beauty, horses have held a unique place in human society and imagination. Elaine Walker tackles the long and multifaceted history of a creature valued for both beauty and usefulness. Spanning the world from the wild steppes of Mongolia to the American plains, Horse chronicles the rich and complex natural history of the animal, from wild feral horses to the domesticated species that once played a central role in daily life as a means of transportation, an instrument of war, and a source of labor. Elaine Walker charts how the long-standing connection between people and horses is reflected in cultures around the world and the implications for both human and animal of such close interaction. She also traces the centrality of the horse in art, entertainment and literature, from the rich global traditions of horse-racing and equestrianism to literary classics such as Follyfoot. Ultimately, Walker contends, the continuing role of the horse in the modern world reveals telling changes in human society."--Publisher's description.